University Students’ Perception About Plickers for Online Formative Assessment Tools - Pebriantika, Erlin; Siswantara, Eka (Universitas Muhammadiyah Mataram, 2023)
Current digital era has influenced the education system to provide technology-oriented activity in the classroom. The development of online formative assessment tools is one of the impacts of this digital revolution. This study aims at providing the perception of the university students on the use of one of online assessment tools called Plickers. The participants of this study consist of 11 pharmacy faculty students who got an English training. The use of Plickers was on their formative assessment of the English training. A semi-structured interview was conducted in order to gain the data. The interview focused on two research questions:(1) How do the university students compare traditional method with Plickers for English formative assessment? and (2) How are their perceptions on Plickers for English formative assessment? The results showed that the students had positive perceptions toward Plickers. When comparing Plickers to the traditional assessment method, the participants found that Plickers was more modern, more fun, and more effective and efficient. This study also elaborates the strength and the weakness of the Plickers in terms of the specific application. These findings could provide more insight on the use of Plickers for the assessment especially in Indonesian education.